Motors of COVID-19 Vaccination Acceptance Scale (MoVac-COVID19S): Evidence of Measurement Invariance Across Five Countries [Corrigendum] - Chen IH; Wu PL; Yen CF; Ullah I; Shoib S; Zahid SU; Bashir A; Iqbal N; Addo FM; Adjaottor ES; Amankwaah GB; Ahorsu DK; et al. (Dove Medical Press, 2022)
Chen IH, Wu PL, Yen CF, et al. Risk Manag Healthc Policy. 2022;15:435–445. Page 437, Materials and Methods, Participants and Recruitment Procedure, Taiwanese Participants section, last sentence, the text “(IRB ref: KMUHIRB-EXEMPT(I)-20200119)” should read “(IRB ref: KMUHIRB-EXEMPT(I)-20200019)”. Page 443, Ethics Approval and Informed Consent section, first line, the text “(IRB ref: KMUHIRB-EXEMPT(I)-20200119)” should read “(IRB ref: KMUHIRB-EXEMPT(I)-20200019)”. The authors apologize for these errors. Read the original article